Sex Differences in Oral Anticoagulation and Outcomes of Stroke and Intracranial Bleeding in Newly Diagnosed Atrial Fibrillation - Yong, Celina M. (J Am Heart Assoc, 2020)
BACKGROUND: Female sex is an independent predictor of stroke in patients with atrial fibrillation (AF). Older data suggest undertreatment with anticoagulation among women compared with men. However, it is unknown if novel therapies and updated guidelines have impacted sex differences in AF treatment and outcomes. METHODS AND RESULTS: We performed a retrospective cohort study of 2.3 million women and men with a new diagnosis of AF and CHA(2)DS(2)‐VASc ≥2 from Marketscan US commercial claims data from 2008 to 2015 to determine whether women with AF remain undertreated and whether this difference mediates observed differences in outcomes. There were 358 649 patients with newly diagnosed AF (43% women). Compared with men, women were older, with higher CHA(2)DS(2)‐VASc scores, and higher comorbidity burden (P<0.0001 for all). Oral anticoagulation‐eligible women with CHA(2)DS(2)‐VASc scores ≥2 were more likely to not receive anticoagulation (50.0% women versus 43.9% men). Women, compared with men, had a higher risk of ischemic stroke (adjusted hazard ratio [aHR], 1.27; 95% CI, 1.21–1.32; P<0.0001) and hospitalization (aHR, 1.06; 95% CI, 1.05–1.07, P<0.0001) but had a lower risk of intracranial bleeding (aHR, 0.91; 95% CI, 0.83–0.99, P=0.03). In mediation analysis, nonreceipt of oral anticoagulation partially mediated the observed increased risk of stroke and decreased risk of intracranial bleeding in women. CONCLUSIONS: In the care of newly diagnosed AF in the United States, women, compared with men, are less likely to receive oral anticoagulation. This appears to mediate the increased risk of both stroke and hospitalization but also appears to mediate lower observed intracranial bleeding risk.